To study the short-term outcome of multimodality treatment on morbidity and quality of life in patients with carcinoma oesophagus - Singh, Karamveer; Jain, Navneet; Saini, Sunil (International Journal of Research in Medical Sciences, 2017)
Background: Oesophageal cancer is sixth most common cause of cancer related deaths worldwide. Despite complete resections, overall survival remained low. To improve the existing treatment combination of chemotherapy and radiotherapy in both neoadjuvant and adjuvant settings was introduced. Impact of treatment on quality of life, morbidities and toxicities associated with multimodality treatment in patients of carcinoma oesophagus was studied prospectively and retrospectively. Methods: A total of 40 patients histologically proven carcinoma of the oesophagus were enrolled in the study. Study included assessment of clinical features, risk factors, biopsy, multimodality treatment and associated morbidities and toxicities. Quality of Life (QOL) in patients of multimodality treatment assessed using European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 and Core 18 before, immediate post treatment and 6 months after completion of the planned treatment. Results: In 40 patients, male to female ratio was 1.10:1. Dysphagia was the leading complain. 3 patients were treated using neoadjuvant therapy (chemotherapy and radiotherapy followed by surgery) among them 2 patients expired, 1 patient is under regular follow up. 6 patients underwent upfront surgery followed by adjuvant therapy out of which 3 patients expired,15 patients were treated with curative intent by definitive chemotherapy and radiotherapy out of which only 7 patients survived for >1 year. 16 patients were treated with palliative intent (radiotherapy, chemotherapy, oesophageal stenting and feeding procedures) in which only 1 patient survived for 1 year. Conclusions: The present study demonstrates that patients over all QOL was reduced after treatment and in the follow up period which was due to the treatment related toxicities but in contrast symptom improvement was observed simultaneously.